LOW MAKING ANALYSIS OF SURAT KETERANGAN PENDUDUK NON PERMANEN (SKPNP) TO STUDENTS (STUDY IN TEMBALANG DISTRICT - Sudarsono, Faizaldi chsan; Priyadi, Budi Puspo (Journal of Public Policy and Management Review, 2019)
Surat Keterangan Penduduk Non Permanen (SKPNP) is a compulsory document for non permanent residents in a certain region. It is regulated in Pemendagri number 14 of 2015 concerning data collection guidelines of non permanent residents. In Semarang city, SKPNP is regulated in local regulation of Semarang city number 4 of 2016 concerning population administration. Semarang city has high urbanization flows because of the facilities provided. One of the facilities is in the field of education. Semarang has a lot of top universities. It caused a lot of students from outside Semarang, even from outside Java island come to Semarang for studying at universities in Semarang. From 16 sub-districts in Semarang, one of them is Tembalang. Tembalang has a lot of universities including Undip and Polines. It caused a lot of students living at dormitory in Tembalang as non-permanent resident although the amount of students who live as permanent residents have high quantity, but the number of SKPNP makers is still very low even in Semarang city. This research uses effectiveness aspects including goals and regulation program aspect, program socialization aspect, program implementation aspect, and program monitoring aspect. The results show the problems that cause low making of SKPNP. The problems are : the regulation that have not been updated, lack of socialization, lack of RT and RW capacity, students who tend to migrate in living, lack of participation from students, and lack of monitoring.